2013
DOI: 10.1155/2013/103830
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antitumor Activity with Combining Effect of mTOR Inhibition and Microtubule Stabilization in Hepatocellular Carcinoma

Abstract: Mammalian target of rapamycin (mTOR) and the microtubules are shown to be potential targets for treating hepatocellular carcinoma (HCC). PI3K/Akt/mTOR activation is associated with resistance to microtubule inhibitors. Here, we evaluated the antitumor activity by cotargeting of the mTOR (using allosteric mTOR inhibitor everolimus) and the microtubules (using novel microtubule-stabilizing agent patupilone) in HCC models. In vitro studies showed that either targeting mTOR signaling with everolimus or targeting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
12
2
Order By: Relevance
“…mTOR activation can promote angiogenesis, tumor invasion, metastasis and the cell cycle. It plays a very important role in the occurrence, development and treatment of liver cancer (43)(44)(45)(46). Signal transducers and activators of transcription3 (STAT3), activation leads to increased expression of downstream target genes, leading to increased cell proliferation, cell survival, angiogenesis and immune system evasion.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR activation can promote angiogenesis, tumor invasion, metastasis and the cell cycle. It plays a very important role in the occurrence, development and treatment of liver cancer (43)(44)(45)(46). Signal transducers and activators of transcription3 (STAT3), activation leads to increased expression of downstream target genes, leading to increased cell proliferation, cell survival, angiogenesis and immune system evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, everolimus was also investigated with low-dose patupilone, with promising results45 reconfirming a synergistic effect between mTOR inhibitors and MBAs in HCC cells. More interestingly, accompanying mechanistic studies demonstrated that the marked antitumor activity of the combination was not affected by further suppression of the mTOR signaling pathway compared with everolimus alone, but may be due to possible induction of apoptosis in these HCC models mediated by the combination treatment 45. The combination was also found to induce a significant reduction in microvessel density in tumors when compared to those treated with vehicle control, indicating potential antiangiogenic activity 45…”
Section: Mbas In Hccmentioning
confidence: 92%
“…Indeed, recent in vivo and in vitro studies have shown that a combination of mTOR inhibitor temsirolimus and low-dose vinblastine had a marked antitumor effect 106. Similarly, everolimus was also investigated with low-dose patupilone, with promising results45 reconfirming a synergistic effect between mTOR inhibitors and MBAs in HCC cells. More interestingly, accompanying mechanistic studies demonstrated that the marked antitumor activity of the combination was not affected by further suppression of the mTOR signaling pathway compared with everolimus alone, but may be due to possible induction of apoptosis in these HCC models mediated by the combination treatment 45.…”
Section: Mbas In Hccmentioning
confidence: 99%
“…Time-lapse imaging of dynamic microtubules al so revealed disorganized movements of the growing microtubule plus-ends in the cellular cortex region, including growth in a direction that is parallel to the cortex. The authors suggested that the functional mTOR-CLIP-170 interaction helps microtubules grow to the cellular cortex [46].…”
Section: The Crosstalk Between Mtor Kinase and Microtubulesmentioning
confidence: 99%